PERLINDUNGAN HUKUM TERHADAP PEKERJA DALAM PERJANJIAN KERJA DENGAN SISTEM OUTSOURCING DI INDONESIA - Dwi Utami, Ida Ayu; Sandi Sudarsana, I Ketut; Darmadha, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 05, Juli 2013)
This paper entitled “Legal Protection To The Workers In Employment Agreement With Outsourcing System in Indonesia”. This paper aims to determine the implementation of the legal relationship between workers and outsourcing services provider. This type of writing is a normative research, which examined with the regulatory approach (the statute approach) means that a issue will be seen from the aspect of the law by reviewing the regulation. Legal relationship between workers and company service providers themselves contained in the employment agreement which contains about rights and obligations between the company and its employees.
Keywords: outsourcing, company, workers